Clinical researchDoes the professional and working context of United Kingdom clinicians predict if they use practices to support patients with long term conditions to self manage? - Kosmala-Anderson, Joanna; Wallace, Louise M.; Turner, Andrew (Archives of Medical Science, 2010)
Introduction : Our study examines how the professional and employment context may influence clinicians’ practice self management support for patients with long term conditions (LTC). Material and methods : We surveyed clinicians working with patients with depression, chronic obstructive pulmonary disorder (COPD), chronic musculo skeletal pain and diabetes. Results : Clinicians most frequently endorsed items on a scale concerned with patient centeredness, and less frequently endorsed items concerned with clinical and organizational self management support. The most important factors predicting these latter activities were the intensity of working experience with patients with LTC and attending professional training addressing the principles and practice of self management support. Practicing patient centeredness was endorsed by nearly all respondents, and so was not sensitive to variation on work variables. Conclusions : The interaction of training and intensity of work with patients with LTC seems to have the most powerful effect on undertaking clinical and organizational self management support practices. To facilitate clinicians’ practice of self management support for patients with LTC it is very important to provide relevant professional training and to build specialized patient care teams with professionals having complimentary skills.